A Biomechanical Investigation of Warm-up Procedures for Musicians - Russell, Donald; McDill, Moyra; Comeau, Gilles; Ahmadi, Nona (CMBES Proceedings, 2012)
Published reports indicate that the rates of physical injury in musicians are surprisingly high and costly. One approach taken to minimize the risk of injury is the use of a proper warm-up prior to either a practice session or a performance. There is a lack of consensus among musicians about the nature and components of a proper warm-up. This paper will examine warm-up for musicians (primarily pianists) from a biomechanical point of view drawing first on information from the fields of performing arts medicine and treatises on music pedagogy to summarize the typical or recommended practices for musicians. The biomechanical facets of these practices are then analyzed to assess their affect the body in the context of the forces and movements required to play an instrument. As there is little research investigating the long term affects of warm-up practices on musicians’ health it is necessary to use results from analogous athletic activities to evaluate the efficacy of the components of warm-up procedures for musicians. As a result of bringing together and analyzing a range of data from a number of different activities we are able to suggest hypotheses regarding important components of warmup for musicians and the impacts of these activities. The results can serve as a basis for looking at long-term effects of warm-up on musicians’ health.